Multiplex Analysis of 230 Medications and 30 Illicit Compounds in Dried Blood Spots and Urine. Issue 6 (4th September 2020) - Tagwerker, Christian; Baig, Irfan; Brunson, Eric J; Dutra-Smith, Davan; Carias, Mary-Jane; de Zoysa, Ranulu S; Smith, David J
Abstract: Drugs of abuse and medication reconciliation testing can benefit from analysis methods capable of detecting a broader range of drug classes and analytes. Mass spectrometry analysis of a wide variety of commonly prescribed medications and over-the-counter drugs per sample also allows for application of a drug–drug interaction (DDI) algorithm to detect adverse drug reactions. In order to prevent adulteration of commonly collected clinical samples such as urine, dried blood spots (DBS) present a reliable alternative. A novel method is described for qualitative and quantitative multiplex analysis of 230 parent drugs, 30 illicit drugs and 43 confirmatory metabolites by HPLC–MS-MS This method is applicable to DBS specimens collected by volumetric absorptive microsamplers and confirmable in urine specimens. A patient cohort ( n = 67) providing simultaneous urine specimens and DBS resulted in 100% positive predictive values of medications or illicits confirmed by detection of a parent drug and/or its metabolite during routine medication adherence analysis. An additional 5, 508 DBS specimens screened ( n = 5, 575) showed 5, 428 (97%) with an inconsistent positive compared to the provided medication list (including caffeine, cotinine or ethanol metabolites), 29 (0.5%) with no medication list and no unexpected positive results (consistent negative) and 22 (0.4%) showed all positive results matching the provided medication list (consistent positive). A DDI algorithm applied to all positive results revealed 17% with serious and 56% with moderate DDI warnings. Comprehensive DBS analysis proves a reliable alternative to urine drug testing for extended medication reconciliation, with the added advantage of detecting DDIs.